Dna, Cell Wall and General Oxidative Damage Underlie the Tellurite/Cefotaxime Synergistic Effect in Escherichia Coli - Vasquez-Guzman, C; Muñoz-Villagran, C; Molina-Quiroz, R (2013)
The constant emergence of antibiotic multi-resistant pathogens is a concern worldwide. An alternative for bacterial treatment using nM concentrations of tellurite was recently proposed to boost antibiotic-toxicity and a synergistic effect of tellurite/cefotaxime (CTX) was described. In this work, the molecular mechanism underlying this phenomenon is proposed. Global changes of the transcriptional profile of Escherichia coli exposed to tellurite/CTX were determined by DNA microarrays. Induction of a number of stress regulators (as SoxS), genes related to oxidative damage and membrane transporters was observed. Accordingly, increased tellurite adsorption/uptake and oxidative injuries to proteins and DNA were determined in cells exposed to the mixture of toxicants, suggesting that the tellurite-mediated CTX-potentiating effect is dependent, at least in part, on oxidative stress. Thus, the synergistic tellurite-mediated CTX-potentiating effect depends on increased tellurite uptake/adsorption which results in damage to proteins, DNA and probably other macromolecules. Our findings represent a contribution to the current knowledge of bacterial physiology under antibiotic stress and can be of great interest in the development of new antibiotic-potentiating strategies. © 2013 Molina-Quiroz et al.